Food deserts in hot arid developing regions: An analysis of food accessibility in Abu Dhabi, UAE - Khaled Alawadi; Nour Alkhaja; Karim Almohtadi (Transportation Research Interdisciplinary Perspectives)
This study examines food environments in nine Abu Dhabi neighborhoods by analyzing food accessibility at neighborhood and superblock scales. Distances from plot centroids to food retail within an 800-m threshold were measured, and food retail locations were classified based on the affordability of fresh produce. Results assessed affordability (dominant closest retail type), proximity (retail count), and diversity (retail type count). Results revealed that while the studied neighborhoods generally do not face issues with physical proximity to food outlets, accessibility challenges in terms of diversity and affordability persist. At the neighborhood scale, food retail density and spatial distribution were the most influential factors, with only two neighborhoods showing limited physical accessibility. Superblock-scale analysis revealed disparities within neighborhoods, with some superblocks in highly accessible neighborhoods having lower levels of food retail accessibility, further proving the impact of the analysis scale on food accessibility assessment. This highlights the importance of dual-scale analysis for capturing local variations in food environments.Principal Component Analysis (PCA) identified land-use mix and food retail density as the most significant urban form attributes, consistently emerging as key factors across all levels of accessibility. Network intersection density and plot attributes also influenced accessibility, though to a lesser extent. The dominance of grocery stores impacts food diversity and affordability, highlighting gaps in Abu Dhabi’s planning policies. These findings provide valuable insights for enhancing food security and refining food retail allocation strategies.